THE FLUENCE OF SHOPEE’S DOUBLE DATE DISCOUNTS ON THE CONSUMPTIVE BEHAVIOUR OF COMMUNICATION SCIENCE STUDENTS AT UNIVERSITY SRIWIJAYA, CLASS OF 2023 - Indrianita, Nadira; Zahra, Syarifah; Razaq, Abdur; Nugraha, Muhamad Yudistira (Jurnal Buana Kata: Pendidikan, Bahasa, dan Ilmu Komunikasi, 2025)
This research aims to analyze the effect of Shopee's "Double Date" discount on the consumer behavior of students of the Communication Science Study Program at Sriwijaya University class of 2023. In the digital era, discount-based promotions are increasingly popular among consumers, especially among students with limited purchasing power. The research method used is a quantitative survey with data collection through questionnaires distributed to 50 students. Data analysis is carried out using a simple linear regression technique to see the relationship between the effect of Shopee discounts and consumptive behavior. Research results show that the "Double Date" discount has a positive and significant influence on students' purchasing decisions, with the main influencing factors being the motivation to get goods at a lower price and social influence from peers. This finding is expected to provide insight for e-commerce platforms and academics in understanding the trend of consumption behavior of the young generation in the digital era.